Structural performance of FCS wall subjected to axial load - Mohamad, Noridah; Goh, Wan Inn; Abdullah, Redzuan; Abdul Samad, Abdul Aziz; Mendis, Priyan; Soﬁ, Massoud (Elsevier Science Ltd, 2017)
The primary purpose of this paper is to present the structural behavior of precast foamed concrete sand-wich walls (FCS) strengthened with double steel shear connectors (DSC) subjected to axial load. The dis-cussion of results addresses the effect of slenderness ratio (H/t) on the behavior of the walls. It also addresses the signiﬁcant effects of using double shear connectors on these behaviors compared to single steel shear connector (SSC). The FCS wall was modeled using ABAQUS and validated by the results from experiment and previous research. Parametric ﬁnite element study (FEA) was conducted by simulating these walls with various H/t under axial load. The structural behavior recorded from FEA includes its ulti-mate load, failure mode, load-deﬂection proﬁles, strain distribution across the wall’s thickness, and ulti-mate shear load. It was found that as H/t increased, the ultimate load decreased but the maximum horizontal deﬂection increased. FCS with H/t 625 failed from crushes and cracks within the top and bot-tom area while FCS with H/t P25 failed from buckling at its mid-height. It was also noticed that FCS with lower H/t experienced more uniform strain distribution across its thickness. FCS with DSC was able to sustain higher load but it deﬂected less compared to walls with SSC, caused by higher stiffness due to larger steel areas. It is interesting to ﬁnd that FCS walls with DSC behaved in a more composite manner and was able to sustain higher ultimate shear force under push of loading test compared to FCS walls with SSC. These ﬁndings show that the FCS wall with DSC is suitable to be used as a load-bearing wall.